The m6A-related mRNA signature predicts the prognosis of pancreatic cancer patients - Meng, Zibo; Yuan, Qingchen; Zhao, Jingyuan; Wang, Bo; Li, Shoukang; Offringa, Rienk; Jin, Xin; Wu, Heshui (Molecular therapy. Oncolytics, 2020)
N6-methyladenosine (m6A) has an important epitranscriptomic modification that controls cancer self-renewal and cell fate. The addition of m6A to mRNA is a reversible modification. The deposition of m6A is encoded by a methyltransferase complex involving three homologous factors, jargonized as “writers,” “erasers,” and “readers.” However, their roles in pancreatic adenocarcinoma (PAAD) are underexploited. With the use of The Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) databases, we provided an mRNA signature that may improve the prognostic prediction of PAAD patients based on the genetic status of m6A regulators. PAAD patients with genetic alteration of m6A regulators had worse disease-free and overall survival. After comparing PAAD groups with/without genetic alteration of m6A regulators, we identified 196 differentially expressed genes (DEGs). Then, we generated a 16-mRNA signature score system through least absolute shrinkage and selection operator (LASSO) Cox regression analysis. Multivariate cox regression analysis demonstrated that a high-risk score significantly correlates with poor prognosis. Moreover, time-dependent receiver operating characteristic (ROC) curves revealed it was effective in predicting the overall survival in both training and validation sets. PAH, ZPLD1, PPFIA3, and TNNT1 from our signature also exhibited an independent prognostic value. Collectively, these findings can improve the understanding of m6A modifications in PAAD and potentially guide therapies in PAAD patients., Pancreatic adenocarcinoma (PAAD) remains a worldwide lethal disease. N6-methyladenosine (m6A) regulators participate in multiple cancers, but its roles in PAAD are underexploited. Meng and his colleagues built a prognostic model based on m6A status using public databases for PAAD patients.